Coeliac disease and microbiota: is it time for personalised biotics intervention? A scoping review - Maureen Leonard; Salvatore Cucchiara; Francesco Valitutti; Elena Cavalli; Beatrice Leter; Fasano Alessio (BMJ Nutrition, Prevention & Health)
Rational A true increase in prevalence of coeliac disease (CeD) has been witnessed worldwide. This ‘on-the-rise’ epidemiological trend for CeD is shared with other immune-mediated disorders and could be due to environment-driven gut microbiota perturbances.Objectives To summarise recent evidence regarding possible relationships between microbiota disturbances and CeD onset, with a specific focus on pathogenesis and possible biotic-based therapeutic interventions.Methods A literature search was launched on 20 August 2024 using Google Scholar, PubMed, EMBASE, Scopus using keywords as follows: celiac disease AND microbiota; celiac disease AND microbiome; celiac disease AND prebiotics; celiac disease AND probiotics; celiac disease AND symbiotics; celiac disease AND postbiotics.Results A total of 1779 articles were retrieved from two authors' blinded search, of which 1297 were duplicates. 206 articles were excluded by abstract as they were commentaries, letters, case series. A final set of 276 articles was suitable for the scope of our review and, after carefully reading the full-text articles, only 131 were considered valuable for the review and included as references for the review.Conclusions While there is extensive literature on microbiota alterations and CeD, lack of clarity remains regarding whether the changes observed in the microbiota of individuals with CeD are effects of the condition or if and how they play a role in its onset. Limited evidence points towards the utility of specific probiotic strains to reduce symptoms, decrease inflammation, support growth in children and overall enhance recovery in CeD.